Non-Canonical Passives - Alexiadou, Artemis; Schäfer, Florian (Linguistik Aktuell/Linguistics Today, 2013)
This paper highlights similarities between two classes of arguably non-canonical passives, namely 'deponent' verbs familiar from Latin, and 'inherent reflexive' verbs in Germanic and Romance, arguing that the latter are the counterparts of the former - notably, both classes of verbs are denominal/deadjectival. Building on the idea that overt morphological voice markings reflect feature distinctions associated with v0 in the syntax, I argue that the special 'unaccusative' morphology (i.e. reflexive or non-active) doesn't just bear on the absence of an external argument in the syntax, but on the presence of an actor-initiation feature of v0 in syntactic configurations lacking an external argument, which accounts for facts such as the ubiquity of reflexive marking across inherent and non-inherent reflexive predicates, and others.